Desempenho de um empilhamento drenado de tubos geotêxteis preenchidos com rejeito de mineração de ouro - Fernanda Taysa de Castro Morais (2020)
Geotextile tubes are an alternative for disposal of mining tailings, allowing the reduction of the area necessary to dispose tailings and reducing the risks of a potential failure. This dissertation aimed to verify the performance of a three-level stacked geotextile tubes filled with fine gold mining tailings. The structure is the large-scale prototype built and evaluated in the work of Freitas Silva (2017) and was installed on the top of a tailings pile located at the Fazenda Brasileiro mine. The structure was monitored and underwent a topographic survey carried out after one year of construction in which it was found that the height of the geotextile tubes did not undergo considerable changes in that period. An exhumation plan for the structure was developed and executed two years after the end of the stack construction. Throughout the exhumation process, the structure was observed regarding deformations, which occurred mainly at the junctions of the geotextile tubes and in the geotextile tube located at the top of the stack. Additionally, aspects of texture, moisture and density of the confined waste were observed, as well as the appearance of the woven geotextile skin. Samples of tailings and woven geotextile were collected from three geotextile tubes selected to be exhumed. The material collected in the field was taken to the laboratory where geotechnical characterization tests were carried out on the tailings, such as specific gravity of tailings particles, size distribution, conventional settlement tests, CIUsat triaxial compression tests, permeability and also microstructural analyzes of tailings particles. The particle-size distribution data was used to evaluate the particle segregation inside the geotextile tubes. However, there was no clear trend in segregation behavior along the axis of the geotextile tubes. The exhumed geotextile had its thickness and mass per unit area measured and was subjected to wide width tensile tests. The results of the tensile tests were analyzed by means of ANOVA statistical tool and the results showed that the geotextile specimens that were exposed to the weather and UV radiation presented the greatest reduction in tensile strength and in elongation at break. Thus, exposure to the sun light and high temperatures in the mining area directly impacted on the geotextile properties.